2011
DOI: 10.5194/acp-11-1313-2011
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic imprints on nitrogen and oxygen isotopic composition of precipitation nitrate in a nitrogen-polluted city in southern China

Abstract: Nitric acid (HNO<sub>3</sub>) or nitrate (NO<sub>3</sub><sup>&minus;</sup>) is the dominant sink for reactive nitrogen oxides (NO<sub>x</sub> = NO + NO<sub>2</sub>) in the atmosphere. In many Chinese cities, HNO<sub>3</sub> is becoming a significant contributor to acid deposition. In the present study, we measured nitrogen (N) and oxygen (O) isotopic composition of NO<sub>3</sub><sup>&minus;</sup> in 113 pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
90
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 57 publications
23
90
1
Order By: Relevance
“…1). This is consistent with back trajectory analysis of NOAA HYSPLIT model, which showed that 62% and 69% of precipitation in 2008 and 2009 were of marine origin, respectively, most of which were transported from the south to Guangzhou city and passed over those former mentioned cities (Fang et al, 2011b).…”
Section: Long-term Changes In Chemical Composition Of Precipitation Isupporting
confidence: 74%
See 1 more Smart Citation
“…1). This is consistent with back trajectory analysis of NOAA HYSPLIT model, which showed that 62% and 69% of precipitation in 2008 and 2009 were of marine origin, respectively, most of which were transported from the south to Guangzhou city and passed over those former mentioned cities (Fang et al, 2011b).…”
Section: Long-term Changes In Chemical Composition Of Precipitation Isupporting
confidence: 74%
“…Ca 2' is mainly derived from alkaline dust, which has many potential sources, including windblown dust and anthropogenic sources such as industrial and construction activities (Larssen and Carmichael, 2000). High Ca deposition in 2005Á2008 in the study city was most likely caused by intensive construction activities in preparation for the 16th Asian Games (Fang et al, 2011b). We suggest that precipitation may become more acidified in the future because the deposition of alkaline dusts containing Ca is also likely to decrease with stricter SO 2 emission control policy and reduced construction activities.…”
Section: Implications For Acid Deposition Controlmentioning
confidence: 99%
“…A sharp decrease in NO3 concentrations was observed after the flooding (Figure ), presumably due to the dilution of the NO3‐rich base‐flow with NO3‐poor rainwater [ Fang et al ., ], which is consistent with the results reported for other watersheds around the world [e.g., Tesi et al ., ]. The large differences in river discharge were expected to increase nutrient input into the PRE [ Lu et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…These changes in emissions may increase the extent of N deposition and thereby alter the acid deposition pattern in the future. This argument is partially supported by the fact that the ratio of equivalent concentrations of SO 2− 4 to NO − 3 in precipitation have gradually decreased from 5.4 to 1.7 in Beijing , and from 4.6 to 1.5 in Guangzhou (Fang et al, 2011) over the last three decades. If this trend continues, HNO 3 is expected to play a more important role than H 2 SO 4 in determining the precipitation acidity in the coming decades.…”
Section: Y P Pan Et Al: Wet and Dry Deposition Of Sulfur In Northementioning
confidence: 96%